ERA DIGITAL PERSEPSI DALAM PARENTING TERHADAP POLA ASUH ANAK DI RA MUBAROKAH - Ulfadhilah, Khairunnisa; Nurkhafifah, Salsabila Dwi (LPPM Universitas Bina Bangsa, 2025)
This study aims to explore the perception of parents in RA Mubarokah towards parenting in the digital era. The research method used is descriptive narrative, which allows researchers to explore the stories and experiences of parents related to the challenges and advantages of parenting in a digital context. In an era where information and communication technology is rapidly developing, parents often face dilemmas in balancing the use of gadgets and children's social interactions. Through in-depth interviews and observations, this study revealed that parents are aware of the importance of guiding children in using technology positively, but are also worried about negative impacts such as the influence of inappropriate content and gadget addiction. The results of the study show that parents in RA Mubarokah apply a more open and communicative parenting approach, where discussions about the use of technology become an important part of parenting. They strive to create healthy boundaries between digital media use and physical activity, and encourage children to engage in activities that support social and emotional development. This research provides insight into how parents' perceptions adapt to changing times and how they try to carry out their role as wise educators and caregivers in the midst of increasingly rapid technological currents. These findings are expected to be a reference for educators and parents in developing effective parenting strategies in the digital era, as well as encourage further discussions on the integration of technology in early childhood education.